HUBUNGAN SOSIO DEMOGRAFI DAN AKSES MEDIA SOSIAL DENGAN PENGETAHUAN PENCEGAHAN COVID-19 PADA MASYARAKAT PESISIR KECAMATAN WAWOLESEA TAHUN 2O2O - Novita Indria Sari; Jumakil Jumakil; Fithria Fithria (FKM Universitas Halu Oleo, 2021)
The Corona virus disease (Covid-19) has been declared a global pandemic by WHO, with an alarming level of spread and severity. In order to break the chain of transmission of Covid-19, a good knowledge of the prevention of Covid-19 is needed in all elements of society so that people are able to make decisions in proper behavior to break the chain of Covid-19 transmission. This study aims to determine the Correlation between socio-demography and social media access with knowledge of Covid-19 prevention in coastal communities in Wawolesea sub-district in 2020. The research method used a cross sectional study approach with a sample of 272 people who were selected by using the Proportional Random Sampling technique. Statistical test using the Chi-square test. The results showed that the knowledge of the coastal community in the wawolesea sub-district about the prevention of Covid-19 was in the quite category of 228 (83.8%) and in the poor category of 44 (16.2%), it was found that there was no correlation between work (p value = 0.657> 0 , 05) with knowledge of Covid-19 prevention, on the other hand there is a correlation between age (p value = 0.000 <0.05), education level (p value = 0.000 <0.05) and access to social media (p value = 0.000 <0, 05 with knowledge of Covid-19 prevention. It is hoped that the local health center should provide more frequent counseling through existing media or making posters about Covid-19 prevention which can be used as information for the public to prevent the incidence of Covid-19.